Welding method to improve the performance of aluminum-silicon coated hot-formed ultra-high-strength steel joints for automobiles

By adding iron-carbon alloy powder when hot-forming ultra-high strength steel for automobile aluminum-silicon plating and using laser welding process, the strength and plastic toughness problems caused by the plating entering the weld are solved, and an efficient and low-cost welding process is achieved, which significantly improves the joint performance.

CN115026429BActive Publication Date: 2025-04-22MID INFRARED LASER RES INST (JIANGSU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210674646.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-15
Publication Date
2025-04-22
Estimated Expiration
2042-06-15

AI Technical Summary

Technical Problem

When welding aluminum-silicon plating for automobiles, ultra-high strength steel is hot-formed, aluminum in the plating is easily entered into the weld, resulting in poor weld strength and plastic toughness. In the prior art, the process of removing the plating increases equipment investment and production auxiliary costs, and reduces production efficiency.

Method used

By adding iron-carbon alloy powder, the alloy composition and amount are controlled, and suitable laser welding technology is adopted to adjust the weld structure, reduce the degree of plating aggregation, and improve the welding quality.

Benefits of technology

It significantly improves the weld structure, improves the strength and plastic toughness of the lap welded joints, simplifies the welding process, reduces production costs and time, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115026429B_ABST
    Figure CN115026429B_ABST
Patent Text Reader

Abstract

A welding method for improving the joint performance of aluminum-silicon-coated hot-formed ultra-high-strength steel for automobiles, wherein two welding samples of aluminum-silicon-coated hot-formed ultra-high-strength steel for automobiles are mounted on a laser welding experimental platform, and the welding parts are overlapped together, and the overlap length is 5-15 mm, and the overlap gap is 0-1 mm; an alloy powder with a particle size of 200-500 mesh is prepared, and the alloy powder is a mixture of carbon-iron powder, and the weight percentage of carbon and iron is respectively: carbon: 20%-60%, iron: 40%-80%; the alloy powder is spread along the weld direction by bonding, and the layer thickness is 30-300 μm; laser welding is performed, the laser incident angle is 85-90°, and the laser power is 1-4 kW; the welding speed is 1-4 m / min, and argon gas with a flow rate of 10-25 L / min is used to protect the molten pool. The method can significantly improve the weld structure and improve the strength of the overlap weld joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding, and in particular relates to a welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high-strength steel joints for automobiles. Background Art

[0002] Lightweighting of automobiles is a hot topic in the current automobile manufacturing industry. Although the use of lightweight materials such as aluminum alloy, magnesium alloy, titanium alloy, composite materials and carbon fiber materials can reduce the weight of the vehicle and reduce fuel consumption, their forming performance, hardness, welding performance, cost and other comprehensive factors cannot match those of steel materials. Therefore, high-strength or ultra-high-strength steel with reduced steel plate thickness is increasingly favored by automobile manufacturers.

[0003] Hot-formed ultra-high-strength boron steel is made by hot-forming technology. The special high-strength boron alloy steel is heated to austenitize, and then quickly cooled. The structure is transformed from austenite to full martensite, and an ultra-high-strength steel plate with a tensile strength of more than 1500MPa can be obtained. In order to prevent the hot-formed ultra-high-strength steel from being oxidized or carbonized during the hot stamping process, a layer of aluminum-silicon coating is usually plated on the surface of the steel plate, thus forming the currently widely used aluminum-silicon coated hot-formed ultra-high-strength steel. However, in the subsequent welding process, since the aluminum in the coating easily enters the weld, segregation is formed in the weld, resulting in poor strength and plastic toughness of the weld. At present, when welding aluminum-silicon coated hot-formed high-strength steel for automobiles, laser cleaning, mechanical grinding, shot peening and other technologies are usually used to remove the coating before welding. Among them, the removal process will increase the investment in equipment, and the removal speed is low, which reduces production efficiency and increases production costs; at the same time, the dust generated after removal needs to be collected and processed, which increases production auxiliary costs.

[0004] At present, the welding of aluminum-silicon coated hot-formed ultra-high-strength steel is mostly focused on the research of the welding (tailoring) process and method of the butt joint welding of aluminum-silicon coated hot-formed ultra-high-strength steel. However, in the actual manufacturing process, it is also common to overlap the hot-formed high-strength steel and use it. From the perspective of the existing technology, there is little research on the lap welding process and method of aluminum-silicon coated hot-formed ultra-high-strength steel, and most of them use pure laser welding and resistance spot welding. Resistance spot welding cannot perform closed welding, and there is a lack of suitable non-destructive testing methods for the joint quality. Although pure laser can perform efficient welding, the aluminum coating entering the weld will reduce the quality of the joint. Therefore, it is urgent to find a welding process and method to improve the performance of the lap weld of aluminum-silicon coated hot-formed ultra-high-strength steel for automobiles.

[0005] According to the welding of lap joints of aluminum-silicon hot-formed ultra-high-strength steel for automobiles, it can be seen that the plate thickness increases after the joint is overlapped, and the four layers of coating of the two layers of plates must be dissolved into the thin and deep weld. By analyzing the organization of the laser lap welded joint, it can be found that the reason for the low mechanical properties of the joint is the formation of high-temperature ferrite in the joint (the reason for the formation of high-temperature ferrite is mainly the dissolution of the Al-based coating, and Al is a stable ferrite forming element). These high-temperature ferrites gather near the weld, and as their focusing degree increases, they will seriously affect the mechanical properties of the joint (high-temperature ferrite is a low-strength and low-toughness phase). In addition to high-temperature ferrite in the weld, there is also martensite transformed from high-temperature austenite. How to reduce the amount of high-temperature ferrite and reduce its focusing degree, and increase the possibility of high-temperature austenite formation, is the key to improving the performance of the joint. According to the Fe-C phase diagram and other materials science related knowledge, carbon is a very good stable austenite forming element, which can form more austenite in the weld during the solidification process, thereby reducing the ferrite formation power and reducing the amount of ferrite formed in the weld. In addition, due to the gaps in welding and the spatter and ablation losses of laser welding, a certain amount of iron needs to be added to the alloy powder to fill the gaps. Based on this, the present invention adds iron-carbon alloy, controls the alloy powder composition and addition amount, and adopts a suitable laser welding process to perform laser lap welding, so as to achieve the purpose of improving the joint performance. Summary of the invention

[0006] In view of the problems existing in the above-mentioned prior art, the present invention provides a welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high-strength steel joints for automobiles. The method can simplify the lap welding process, has low implementation cost, and can improve production efficiency. At the same time, it can significantly improve the weld structure and improve the strength of the lap weld joint.

[0007] In order to achieve the above object, the present invention provides a welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high-strength steel joints for automobiles, comprising the following steps:

[0008] Step 1: First, pre-treat the aluminum-silicon coated hot-formed ultra-high-strength steel, then mount two welding specimens of aluminum-silicon coated hot-formed ultra-high-strength steel for automobiles on the laser welding experimental platform, and overlap the welding parts to form a welded part; the overlap length of the welded part is 5 to 15 mm, and the overlap gap is 0 to 1 mm;

[0009] Step 2: preparing alloy powder, the alloy powder has a particle size of 200-500 meshes, which is a mixture of carbon and iron powders, and the weight percentages of carbon and iron are: carbon: 20%-60%, iron: 40%-80%;

[0010] Step 3: Spread the alloy powder along the weld direction by bonding, with the thickness of the layer being 30 to 300 μm;

[0011] Step 4: Use laser welding. During welding, the incident angle of the laser is 85-90°, the laser power is 1-4kw; the welding speed is 1-4m / min, and argon gas is used to protect the molten pool, and the gas flow rate of the protective gas is 10-25L / min.

[0012] The preprocessing method in step 1 is as follows:

[0013] First, use a cotton ball dipped in an organic solvent to wipe the front and back surfaces of the hot-formed high-strength steel to remove surface impurities; then quickly blow dry the wiped hot-formed high-strength steel, and then place it in a dry place for welding.

[0014] In step 1, the organic solvent is acetone or ethanol.

[0015] In step 1, the overlap length is 10 mm and the overlap gap is 0.1 mm.

[0016] In step 4, the incident angle of the laser is 85°; the flow rate of the protective gas is 15 L / min.

[0017] In step 2, the weight percentage contents of carbon and iron are: carbon: 20%, iron: 80%; in step 3, the thickness of the layer is 100 μm; in step 4, the particle size of the alloy powder is 300 mesh; the laser power is 2 kW; and the welding speed is 1 m / min.

[0018] In step 2, the weight percentage contents of carbon and iron are: carbon: 35%, iron: 65%; in step 3, the thickness of the layer is 150 μm; in step 4, the particle size of the alloy powder is 300 mesh; the laser power is 4 kW; and the welding speed is 3 m / min.

[0019] In the present invention, the problem of slight collapse of pure laser welding joints is solved by adding alloy components, thereby improving the forming quality and obtaining high-quality lap joints. More importantly, due to the addition of alloy components during the welding process, the formation of ferrite is suppressed, the aggregation of ferrite is effectively alleviated, and the mechanical properties of the lap joint are significantly improved. This method can adjust the weld structure by controlling the composition and addition amount of the alloy, and cooperate with the laser welding process, thereby reducing the aggregation degree of the coating in the weld, especially reducing the aggregation degree of the coating at the fusion line, so as to obtain a higher strength lap joint. This method can be used to obtain a well-formed and excellent performance aluminum-silicon coated hot-formed ultra-high strength steel laser lap welding weld, which is particularly suitable for the welding of aluminum-silicon coated hot-formed ultra-high strength steel lap joints for automobiles. Compared with the traditional method, the present invention does not need to remove the aluminum-silicon coating on the surface of the hot-formed high-strength steel, simplifies the lap welding process, improves production efficiency, and significantly improves the weld structure and the strength of the lap welding joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of laser welding assembly in which alloy powder is added to improve the performance of lap joints of hot-formed ultra-high-strength steel with aluminum-silicon coating for automobiles in the present invention. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings:

[0022] like Figure 1 As shown, the present invention provides a welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high-strength steel joints for automobiles, comprising the following steps:

[0023] Step 1: First, pre-treat the aluminum-silicon coated hot-formed ultra-high-strength steel, then mount two welding specimens of aluminum-silicon coated hot-formed ultra-high-strength steel for automobiles on the laser welding experimental platform, and overlap the welding parts to form a welded part; the overlap length of the welded part is 5 to 15 mm, and the overlap gap is 0 to 1 mm;

[0024] As a preferred embodiment, the thickness of the aluminum-silicon coated hot-formed ultra-high strength steel is 0.5 to 3 mm, and the thickness of the aluminum-silicon coating in the aluminum-silicon coated hot-formed ultra-high strength steel is 20 to 40 μm;

[0025] Step 2: preparing alloy powder, the alloy powder has a particle size of 200-500 meshes, which is a mixture of carbon and iron powders, and the weight percentages of carbon and iron are: carbon: 20%-60%, iron: 40%-80%;

[0026] Step 3: Spread the alloy powder along the weld direction by bonding, with the thickness of the layer being 30 to 300 μm;

[0027] Step 4: Use laser welding. During welding, the incident angle of the laser is 85-90°, the laser power is 1-4kw; the welding speed is 1-4m / min, and argon gas is used to protect the molten pool, and the gas flow rate of the protective gas is 10-25L / min.

[0028] The preprocessing method in step 1 is as follows:

[0029] First, use a cotton ball dipped in an organic solvent to wipe the front and back surfaces of the hot-formed high-strength steel to remove surface impurities; then quickly blow dry the wiped hot-formed high-strength steel, and then place it in a dry place for welding.

[0030] In step 1, the organic solvent is acetone or ethanol.

[0031] In step 1, the overlap length is 10 mm and the overlap gap is 0.1 mm.

[0032] In step 4, the incident angle of the laser is 85°; the flow rate of the protective gas is 15 L / min.

[0033] In step 2, the weight percentage contents of carbon and iron are: carbon: 20%, iron: 80%; in step 3, the thickness of the layer is 100 μm; in step 4, the particle size of the alloy powder is 300 mesh; the laser power is 2 kW; and the welding speed is 1 m / min.

[0034] In step 2, the weight percentage contents of carbon and iron are: carbon: 35%, iron: 65%; in step 3, the thickness of the layer is 150 μm; in step 4, the particle size of the alloy powder is 300 mesh; the laser power is 4 kW; and the welding speed is 3 m / min.

[0035] During welding, the laser welding system is started, the base material is melted by laser, and a weld is formed after cooling. The present invention is further described below in conjunction with embodiments.

[0036] Embodiment 1:

[0037] The aluminum-silicon coated ultra-high strength steel that has been pre-treated before welding is hot-formed according to Figure 1 As shown in the figure, the lap joint is assembled, and the alloy powder with the alloy composition of 20% carbon and 80% iron with a particle size of 300 mesh is bonded with a binder and spread on the weld bead with a thickness of 100μm. The lap length of the joint is 10mm, the lap gap is 0.1mm, the laser incident angle is 85°, the laser power is 2kW, the welding speed is 1m / min, and when argon is used for protection, the argon flow rate is 15L / min for laser welding.

[0038] The results show that after welding, the entire weld is well formed, without spatter, and is a full penetration weld. The center of the weld is martensite and a very small amount of ferrite; the heat affected zone is divided into four parts, namely the coarse-grained heat affected zone and the fine-grained heat affected zone near the weld (the structure is mainly lath martensite), the mixed heat affected zone (the structure is martensite and ferrite) and the tempering zone (the structure is tempered martensite); the tempering zone is a softening zone with lower hardness. The weld of this process was tested by tensile testing, and the joint broke at the fusion line; the tensile strength of the joint can reach 701MPa, which is higher than the strength of the lap joint without adding alloy powder (about 450MPa).

[0039] Embodiment 2:

[0040] The aluminum-silicon coated ultra-high strength steel that has been pre-treated before welding is hot-formed according to Figure 1As shown in the figure, the lap joint is assembled, and the alloy powder with a composition of 35% carbon and 65% iron with a particle size of 500 mesh is bonded with a binder and spread on the weld with a length of 150μm. The lap length of the joint is 10mm, the lap gap is 0.1mm, the laser incident angle is 85°, the laser power is 4kW, the welding speed is 3m / min, and when argon is used for protection, the argon flow rate is 15L / min for laser welding.

[0041] The results show that after welding, the entire weld is well formed, without spatter, and is a full penetration weld. The center of the weld is martensite and a very small amount of ferrite; the heat affected zone is divided into four parts, namely the coarse-grained heat affected zone and the fine-grained heat affected zone near the weld (the structure is mainly lath martensite), the mixed heat affected zone (the structure is martensite and ferrite) and the tempering zone (the structure is tempered martensite); the tempering zone is a softening zone with lower hardness. The weld of this process was tested by tensile testing, and the joint broke at the fusion line; the tensile strength of the joint can reach 746MPa, which is higher than the strength of the lap joint without alloy powder (about 450MPa).

[0042] According to the welding of lap joints of aluminum-silicon hot-formed ultra-high-strength steel for automobiles, it can be seen that the plate thickness increases after the joint is overlapped, and the four layers of coating of the two layers of plates must be dissolved into the thin and deep weld. By analyzing the organization of the laser lap welded joint, it can be found that the reason for the low mechanical properties of the joint is the formation of high-temperature ferrite in the joint (the reason for the formation of high-temperature ferrite is mainly the dissolution of the Al-based coating, and Al is a stable ferrite forming element). These high-temperature ferrites gather near the weld, and as their focusing degree increases, they will seriously affect the mechanical properties of the joint (high-temperature ferrite is a low-strength and low-toughness phase). In addition to high-temperature ferrite in the weld, there is also martensite transformed from high-temperature austenite. How to reduce the amount of high-temperature ferrite and reduce its focusing degree, and increase the possibility of high-temperature austenite formation, is the key to improving the performance of the joint. According to the Fe-C phase diagram, carbon is a very good stable austenite forming element, which can form more austenite in the weld during the solidification process, thereby reducing the ferrite formation power and reducing the amount of ferrite formed in the weld. In addition, due to the gaps in welding and the spatter and ablation losses of laser welding, a certain amount of iron needs to be added to the alloy powder to fill the gaps. Based on this, the present invention adds iron-carbon alloy, controls the alloy powder composition and addition amount, and adopts a suitable laser welding process to perform laser lap welding, so as to achieve the purpose of improving the joint performance.

[0043] The present invention solves the problem of slight collapse of pure laser welding joints by adding alloy components, thereby improving the forming quality and obtaining high-quality lap joints. More importantly, due to the addition of alloy components during the welding process, the formation of ferrite is suppressed, the aggregation of ferrite is effectively alleviated, and the mechanical properties of the lap joint are significantly improved. This method can adjust the weld structure by controlling the composition and addition amount of the alloy, and cooperate with the laser welding process, thereby reducing the aggregation degree of the coating in the weld, especially reducing the aggregation degree of the coating at the fusion line, so as to obtain a higher strength lap joint. This method can be used to obtain a well-formed and excellent performance aluminum-silicon coated hot-formed ultra-high-strength steel laser lap welding weld, which is particularly suitable for the welding of aluminum-silicon coated hot-formed ultra-high-strength steel lap joints for automobiles. Compared with the traditional method, the present invention does not need to remove the aluminum-silicon coating on the surface of the hot-formed high-strength steel, simplifies the lap welding process, improves production efficiency, and significantly improves the weld structure and increases the strength of the lap weld joint.

Claims

1. A welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high strength steel joints for automobiles, characterized in that: The steps include: Step 1: First, pre-treat the aluminum-silicon coated hot-formed ultra-high-strength steel, then mount two welding specimens of aluminum-silicon coated hot-formed ultra-high-strength steel for automobiles on the laser welding experimental platform, and overlap the welding parts to form a welded part; the overlap length of the welded part is 10 mm, and the overlap gap is 0.1 mm; Step 2: preparing alloy powder, the alloy powder has a particle size of 500 mesh, which is a mixture of carbon and iron powders, and the weight percentages of carbon and iron are: carbon: 35%, iron: 65%; Step 3: Spread the alloy powder along the weld direction by bonding, with a layer thickness of 150 μm; Step 4: Use laser welding. During welding, the laser incident angle is 85° and the laser power is 4kw. The welding speed is 3m / min, and argon gas is used to protect the molten pool. The gas flow rate of the protective gas is 15L / min.

2. A welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high strength steel joints for automobiles according to claim 1, characterized in that: The preprocessing method in step 1 is as follows: First, use a cotton ball dipped in an organic solvent to wipe the front and back surfaces of the aluminum-silicon coated hot-formed ultra-high-strength steel to remove surface impurities; then quickly blow dry the wiped hot-formed high-strength steel, and then place it in a dry place for welding.

3. A welding method for improving the performance of aluminum-silicon coated hot-formed ultra-high strength steel joints for automobiles according to claim 2, characterized in that: In step 1, the organic solvent is acetone or ethanol.

Citation Information

Patent Citations

  • Method for improving performance of aluminum-silicon coating hot-formed ultrahigh-strength steel laser welding head

    CN114346439A